2019
DOI: 10.1097/ftd.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Catalase C-262T Polymorphism Is a Risk Factor for Valproic Acid–Induced Abnormal Liver Function in Chinese Patients With Epilepsy

Abstract: Background: Individual susceptibility to valproic acid (VPA)-caused hepatotoxicity might result from genetic deficiencies in the detoxification and antioxidant enzymes including glutathione S-transferases (GSTs), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx). This study aimed to investigate the relationships between GST mu 1 (GSTM1), GST theta 1 (GSTT1), CAT C-262T, GPx1 Pro200Leu, and SOD2 Val16Ala polymorphisms and the risk of abnormal liver function in Chinese epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…However, in this study the increase in Nrf2 protein expression did not induce an increase in MnSOD gene expression (Figure 4D and 4.8). In contrast; both GPx (Figure 4E) and catalase (Figure 4C) that function to detoxify H 2 O 2 to H 2 O were increased 33 . Collectively, these results suggest an increase in free radical production and an antioxidant response mounted against it that was inadequate in the prevention of acute oxidative stress.…”
Section: Discussionmentioning
confidence: 90%
“…However, in this study the increase in Nrf2 protein expression did not induce an increase in MnSOD gene expression (Figure 4D and 4.8). In contrast; both GPx (Figure 4E) and catalase (Figure 4C) that function to detoxify H 2 O 2 to H 2 O were increased 33 . Collectively, these results suggest an increase in free radical production and an antioxidant response mounted against it that was inadequate in the prevention of acute oxidative stress.…”
Section: Discussionmentioning
confidence: 90%
“…Meanwhile, superoxide dismutase 2 (SOD2) polymorphism was also tested for its potential risk for liver damage, and found that SOD2 Val/Val contributed to VPA-induced liver dysfunction with an elevated γ-glutamyltransferase levels (Saruwataria et al, 2012). Furthermore, catalase (CAT) genotype was reported as a significant genetic risk factor for VPA-induced liver dysfunction, and CAT C-262T carriers exhibited an increased risk of developing abnormal hepatic function compared with the non-carriers (OR=3.968, P = 0.003) (Ma et al, 2019). These findings raise the possibility that GSTs, SOD2 and CAT may be implicated in VPA -induced hepatotoxicity for their roles on the liver oxidative stress.…”
Section: Genetic Biomarkers For Vpa-induced Liver Injurymentioning
confidence: 93%
“…Èçìåí÷èâîñòü ãåíîòèïíûõ ñâîéñòâ ãåíîâ àíòèîêñèäàíòíîé ñèñòåìû øèðîêî èçó÷åíà è èññëåäîâàíà ó ïàöèåíòîâ ñ ýíäîêðèííûìè, ñåðäå÷íî-ñîñóäèñòûìè, íåéðîäåãåíåðàòèâíûìè, ãèíåêîëîãè÷åñêèìè, îôòàëüìîëî-ãè÷åñêèìè è äðóãèìè çàáîëåâàíèÿìè. Ïðè ýòîì óñòàíîâëåíà ñîïðÿaeåííîñòü åäèíè÷íûõ ïîëèìîðôèçìîâ íåêîòîðûõ ãåíîâ, êîäèðóþùèõ ïðîäóêöèþ ÑÎÄ, êàòàëàçû è ãëóòàòèîí-S-òðàíñôåðàçû ñ ðèñêîì èõ ðàçâèòèÿ è ïðîãðåññèðîâàíèÿ [14,15,16].…”
Section: ðåçóëüòàòû è èõ îáñóAeäåíèåunclassified